Effect of 2-Weeks Ischemic Preconditioning on Exercise Performance: A Pilot Study - Tanaka, Daichi; Suga, Tadashi; Shimoho, Kento; Isaka, Tadao (Frontiers in Sports and Active Living, 2021)
An acute bout of ischemic preconditioning (IPC) has been reported to increase exercise performance. Nevertheless, the ineffectiveness of acute IPC on exercise performance has also been reported. Similarly, the effect of a shot-term intervention of IPC on exercise performance remains controversial in previous studies. In this study, we examined the effects of short-term IPC intervention on whole and local exercise performances and its-related parameters. Ten healthy young males undertook a 2-weeks IPC intervention (6 days/weeks). The IPC applied to both legs with three episodes of a 5-min ischemia and 5-min reperfusion cycle. Whole-body exercise performance was assessed by peak O2 consumption (VO2: VO2peak) during a ramp-incremental cycling test. Local exercise performance was assessed by time to task failure during a knee extensor sustained endurance test. A repeated moderate-intensity cycling test was performed to evaluate dynamics of pulmonary VO2 and muscle deoxygenation. The knee extensor maximal voluntary contraction and quadriceps femoris cross-sectional area measurements were performed to explore the potentiality for strength gain and muscle hypertrophy. The whole-body exercise performance (i.e., VO2peak) did not change before and after the intervention (P = 0.147, Power = 0.09, Effect size = 0.21, 95% confidence interval: −0.67, 1.09). Moreover, the local exercise performance (i.e., time to task failure) did not change before and after the intervention (P = 0.923, Power = 0.05, Effect size = 0.02, 95% confidence interval: −0.86, 0.89). Furthermore, no such changes were observed for all parameters measured using a repeated moderate-intensity cycling test and knee extensor strength and quadriceps femoris size measurements. These findings suggest that a 2-weeks IPC intervention cannot increase whole-body and local exercise performances, corresponding with ineffectiveness on its-related parameters in healthy young adults. However, the statistical analyses of changes in the measured parameters in this study showed insufficient statistical power and sensitivity, due to the small sample size. Additionally, this study did not include control group(s) with placebo and/or nocebo. Therefore, further studies with a larger sample size and control group are required to clarify the present findings.